2020
DOI: 10.1111/idh.12434
|View full text |Cite
|
Sign up to set email alerts
|

Dental hygiene graduates’ educational preparedness: Self‐confidence ratings of the CDHA baccalaureate competencies

Abstract: PurposeIn 2015, the Canadian Dental Hygienists Association (CDHA) published the first Canadian Competencies for Baccalaureate Dental Hygiene Programs (CCBDHP). To date, there is little evidence to support that baccalaureate graduates have gained these abilities. The purpose of the study was to investigate the confidence levels of baccalaureate graduates in their ability to demonstrate the CCBDHP.MethodsAn online, anonymous study was conducted with the 2013‐2016 graduates of the University of British Columbia t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 44 publications
0
14
0
1
Order By: Relevance
“…Sunnell and colleagues [ 35 ] study supports this finding, citing the dental hygiene graduates felt more confident in health promotion at an individual level rather than a community level. Dental professionals may feel more confident in behavioural approaches to health promotion, as there has been evidence to support the increased amount of time spent on a topic in university education increases professional confidence [ 35 ].…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…Sunnell and colleagues [ 35 ] study supports this finding, citing the dental hygiene graduates felt more confident in health promotion at an individual level rather than a community level. Dental professionals may feel more confident in behavioural approaches to health promotion, as there has been evidence to support the increased amount of time spent on a topic in university education increases professional confidence [ 35 ].…”
Section: Discussionmentioning
confidence: 81%
“…Sunnell and colleagues [ 35 ] study supports this finding, citing the dental hygiene graduates felt more confident in health promotion at an individual level rather than a community level. Dental professionals may feel more confident in behavioural approaches to health promotion, as there has been evidence to support the increased amount of time spent on a topic in university education increases professional confidence [ 35 ]. Studies, which have reported on the health promotion preparation of oral health professionals, have highlighted that the training focuses mainly on education or behaviour change approach, such as, providing oral hygiene instructions to patients in hospitals and delivering health education sessions [ 36 38 ].…”
Section: Discussionmentioning
confidence: 81%
“…Sunnell and colleagues (34) study supports this nding, citing the dental hygiene graduates felt more con dent in health promotion at an individual level rather than a community level. Dental professionals may feel more con dent in behavioural approaches to health promotion, as there has been evidence to support the increased amount of time spent on a topic in university education increases professional con dence (34). Studies, which have reported on the health promotion preparation of oral health professionals, have highlighted that the training focuses mainly on education or behaviour change approach, such as, providing oral hygiene instructions to patients in hospitals and delivering health education sessions (35)(36)(37).…”
Section: Health Educationmentioning
confidence: 99%
“…The only study related to this new competency standard was conducted concurrently with this study at the University of British Columbia (UBC) with program graduates from 2013 to 2016. 7 It is recognized that learners are evaluated to competence through many different types of authentic assessments including self, peer, and faculty assessments. 7,8 However, exploring the self-confidence of senior baccalaureate students provides a different lens through which to gain insights into their abilities.…”
Section: Introductionmentioning
confidence: 99%
“…7 It is recognized that learners are evaluated to competence through many different types of authentic assessments including self, peer, and faculty assessments. 7,8 However, exploring the self-confidence of senior baccalaureate students provides a different lens through which to gain insights into their abilities. Such an investigation was deemed important given that self-confidence is associated with professional competence.…”
Section: Introductionmentioning
confidence: 99%